Haemodynamic management of patients with left ventricular assist devices using echocardiography: the essentials. (30th January 2019) - Bouchez, Stefaan; Van Belleghem, Yves; De Somer, Filip; De Pauw, Michel; Stroobandt, Roland; Wouters, Patrick
Abstract: Mechanical circulatory support with continuous-flow left ventricular assist devices (LVADs) has emerged as a viable treatment modality for patients with advanced heart failure. LVAD support results in unique haemodynamic and echocardiographic alterations that must be understood to provide optimal care for these patients. In this review, we propose essential echocardiographic and haemodynamic elements for the assessment of optimal LVAD function based on the literature and the use of simulation software. A key element of LVAD physiology remains the interaction between an unloaded left ventricle and a loaded right ventricle. The echocardiographic assessment and treatment of the pathophysiology of the right-sided part of the heart remains critical to maintaining optimal LVAD support.